2018
DOI: 10.1038/s41467-018-05531-8
|View full text |Cite
|
Sign up to set email alerts
|

Dipolar cations confer defect tolerance in wide-bandgap metal halide perovskites

Abstract: Efficient wide-bandgap perovskite solar cells (PSCs) enable high-efficiency tandem photovoltaics when combined with crystalline silicon and other low-bandgap absorbers. However, wide-bandgap PSCs today exhibit performance far inferior to that of sub-1.6-eV bandgap PSCs due to their tendency to form a high density of deep traps. Here, we show that healing the deep traps in wide-bandgap perovskites—in effect, increasing the defect tolerance via cation engineering—enables further performance improvements in PSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
244
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(262 citation statements)
references
References 60 publications
12
244
0
Order By: Relevance
“…It should be noted that compared with the film without FA + , the FA + incorporated films exhibit a blueshift of the absorption on‐set from 684 nm in MAPb(I 0.6 Br 0.4 ) 3 to 670 nm in MA 0.7 FA 0.3 Pb(I 0.6 Br 0.4 ) 3 . Similar phenomenon has also been reported by Sargent and co‐workers, and they have found that it is due to the crystal distortion caused by the size difference between the organic cations and halide anions 25,35,45…”
Section: Device Performance Of Pvscs Prepared With Different Perovskisupporting
confidence: 83%
See 2 more Smart Citations
“…It should be noted that compared with the film without FA + , the FA + incorporated films exhibit a blueshift of the absorption on‐set from 684 nm in MAPb(I 0.6 Br 0.4 ) 3 to 670 nm in MA 0.7 FA 0.3 Pb(I 0.6 Br 0.4 ) 3 . Similar phenomenon has also been reported by Sargent and co‐workers, and they have found that it is due to the crystal distortion caused by the size difference between the organic cations and halide anions 25,35,45…”
Section: Device Performance Of Pvscs Prepared With Different Perovskisupporting
confidence: 83%
“…It is corresponding to around 30% of Br − to the total halide composition 34. However, such high Br − content would cause phase impurity and high defect density issues in the resulting films, which are detrimental to the device performances 14,35,36. Sutter‐Fella et al reported that incorporating Br − will induce defects close to the mid‐gap of the perovskites using sub‐bandgap external quantum efficiency (EQE) measurement, and the defect density increases with increasing the Br − content 31.…”
Section: Device Performance Of Pvscs Prepared With Different Perovskimentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing a highly polar additive formamide (CH 3 NO) into the precursor solution, the solubility of the Cs salt increased, which led to the less formation of yellow δ‐phases and reduced defects density in films. As a result, the optimized FA 0.83 Cs 0.17 Pb(I 0.6 Br 0.4 ) 3 PSC ( E g = 1.75 eV) exhibited a high stability and reduced hysteresis, with PCE of 17.8% and a V OC of 1.23 V. Recently, Tan et al showed that the presence and reorientation of the MA dipolar cation in CsFA‐based perovskites could heal the deep trap defects and then reduce the trap‐assisted nonradiative recombination. Via cation engineering, the Cs 0.05 MA 0.15 FA 0.8 Pb(I 0.75 Br 0.25 ) 3 ( E g = 1.65 eV) with an illumination area of 1.1 cm 2 delivered a stabilized PCE of 20.7%, a high V OC of 1.22 V and a low V OC deficit of 0.41 V. The Cs 0.12 MA 0.05 FA 0.83 Pb(I 0.6 Br 0.4 ) 3 perovskite ( E g = 1.74 eV) yielded an efficiency of 19.1%, with a high V OC of 1.25 V and FF of 81.5%.…”
Section: Current Research Trends In Tandem Devicesmentioning
confidence: 98%
“…[26] Li et al invented a novel gradient thermal annealing to control the growth of CsPbI 2 Br film (band gap = 1.92 eV), and a champion PCE of 16.07% with a V OC of 1.23 V was realized. [29] It can be found that the opencircuit voltage loss (V oc loss) is still the main reason of low performance of inorganic perovskite solar cells, which strongly related to energy band matching and defects at the interface or in the bulk of perovskite. [28] Although there are significant progresses in inorganic perovskite solar cells, the PCE is still far behind the hybrid PSCs, even compared with the I-Br mixed hybrid perovskite with a similar band gap (1.75 eV).…”
mentioning
confidence: 99%